2021
DOI: 10.1101/2021.12.05.21267216
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic Subgroups Inform on Pathobiology in Adult and Pediatric Burkitt Lymphoma

Abstract: Burkitt lymphoma (BL) accounts for the majority of pediatric non-Hodgkin lymphomas (NHL) and is relatively rare but significantly more lethal when diagnosed in adults. The global incidence is highest in Sub-Saharan Africa, where Epstein-Barr virus (EBV) positivity is observed in 95% of all tumors. Both pediatric (pBL) and adult (aBL) cases are known to share some driver mutations, for example MYC translocations, which are seen in > 90% of cases. Sequencing efforts have identified many common somatic alterat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…This idea was also supported by findings that somatic mutations in ID3, TCF3, CCND3, and SOX11 genes were detected more frequently in pediatric BL patients than adult cases [82], which agrees with the EBV data discussed above. Independent support for this idea has been reported in a study of 230 BL cases from Africa, the US, Germany, and Brazil, which showed distinct somatic mutations in pediatric cases (ARID1A) versus adult cases (TET2) [84]. A promising area of research is to elucidate the molecular basis of multimodality of BL in regional and global datasets.…”
Section: Discussionmentioning
confidence: 86%
“…This idea was also supported by findings that somatic mutations in ID3, TCF3, CCND3, and SOX11 genes were detected more frequently in pediatric BL patients than adult cases [82], which agrees with the EBV data discussed above. Independent support for this idea has been reported in a study of 230 BL cases from Africa, the US, Germany, and Brazil, which showed distinct somatic mutations in pediatric cases (ARID1A) versus adult cases (TET2) [84]. A promising area of research is to elucidate the molecular basis of multimodality of BL in regional and global datasets.…”
Section: Discussionmentioning
confidence: 86%
“…Due to MYC mutation, proliferation and apoptosis are uncoupled, consequently proliferation is stimulated and apoptosis abrogated. Deregulation and progression of cell cycle is augmented by several mutations, for example by a mutation in CCND3, TCF3, ID3, and TP53 9,26,34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…The relevance of this finding is underlined by the findings from refs. 35,51 , which were published during the revision of this study 36,51 . Both studies show the negative impact of TP53 mutations on survival.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the emerging genetic subgrouping systems for lymphomas rely on the presence of specific driver mutations (including SVs and CNAs) and patterns of SHM. 187,[409][410][411] SVs involving an oncogene and an active regulatory element causing ectopic oncogene expression (eg, BCL2) or those forming a functional fusion gene (eg, NPM1::ALK) can be diagnostic, prognostic, or predictive for targeted therapies. For oncogenes having promiscuous rearrangement partners (eg, MYC, BCL6), the identity of partners may have a differential influence on prognosis.…”
Section: Wgs: Ongoing Opportunities For Discoverymentioning
confidence: 99%